Sargassum pallidum reduces inflammation to exert antidepressant effect by regulating intestinal microbiome and ERK1/2/P38 signaling pathway - Su, Dan; Li, Qianmin; Lai, Xin; Song, Yonggui; Li, Huizhen; Ai, Zhifu; Zhang, Qi; Shao, Wenxiang; Yang, Ming; Zhu, Genhua (Frontiers in Pharmacology, 2024)
Immune inflammation is one of the main factors in the pathogenesis of depression. It is an effective and active way to find more safe and effective anti-inflammatory depressant drugs from plant drugs. The purpose of this study is to explore the potential of marine plant Sargassum pallidum(Turn).C.Ag.(Haihaozi, HHZ) in the prevention and treatment of depression and to explain the related mechanism.Phytochemical analysis showed that alkaloids, terpenes, and organic acids are the main constituents. In vitro and in vivo activity studies showed the anti-neuroinflammatory and antidepressant effect of Sargassum pallidum, furthermore, confirmed that 7-Hydroxycoumarin, Scoparone, and Kaurenoic Acid are important plant metabolites in Sargasum pallidum for anti-neuroinflammation. Mechanism exploration showed that inhibition of ERK1/2/p38 inflammatory signaling pathway contributing to the antidepressant effect of Sargassum pallidum in reducing intestinal inflammatory levels. This study confirmed the value of Sargassum pallidum and its rich plant metabolites in anti-inflammatory depression, providing a new choice for the follow-up research and development of antidepressant drugs.